Analisis Persepsi Pelaku dan Konsumen Terhadap Tantangan dan Peluang UMKM Buah Potong di Baruga Street Food Kota Palu - Bahtiar Bahtiar; Nazwa Nazwa; Elin Elin; Suasa Suasa; Dandan Haryono; Nurhayati Hamid (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This study aims to analyze the condition of Micro, Small, and Medium Enterprises (MSMEs) selling cut fruit at Baruga Street Food in Palu City through abased on the perceptions of business actors and consumers. MSMEs play a vital role in thelocal economy, but face various challenges, making strategic analysisessential. This study uses a descriptive qualitative approachwith data collection techniques in the form of in-depth interviews, observation,and documentation. Data analysis was carried out through reduction, presentation, andconclusion drawing based on the SWOT framework. The results of the study showthat the main Strengths of MSMEs lie in theirstrategic business locations and the fresh quality of their products, supported by the trend towards healthy lifestyles. Meanwhile, their Weaknesses include limitedcapital, the short shelf life of fruit, and an incomplete variety of fruit.The greatest Opportunities are marketing expansion throughdigital platforms (Gojek/Instagram), product innovation, and the development of adelivery system. External Threats include intense business competitionand fluctuations in raw material prices. Overall, the fruit-cutting MSMEs at Baruga Street Food has strong potential for growth, butrequires a strategic focus on optimizing stock management, product diversification, and utilizing digital opportunities to strengthen competitiveness andmarket reach.